2021
DOI: 10.1371/journal.pntd.0010026
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of soil-transmitted helminth infections, schistosomiasis, and lymphatic filariasis before and after preventive chemotherapy initiation in the Philippines: A systematic review and meta-analysis

Abstract: Objective To estimate the impact of preventive chemotherapy on the prevalence and intensity of soil-transmitted helminth (STH) infections, schistosomiasis, and lymphatic filariasis in the Philippines, using systematic review and meta-analysis. Methods We included reports reporting prevalence of STH infections, schistosomiasis, or lymphatic filariasis in the Philippines published until 31 March 2021. Peer-reviewed studies were identified in electronic databases. Grey literature reports by the University of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The 2 nd highest number of cases from 2009 to 2013 was in Eastern Visayas, which is also endemic for soil-transmitted helminthiases (Leyte) and is the top region with poor sanitation. 44 The UNICEF has reported that sanitation targets in the Philippines, together with the rest of the world, are off-track from the goal to provide sanitation for all by 2030. 45 A recent typhoon in Southern Leyte required concerted efforts to restore access to clean water and sanitation facilities.…”
Section: Discussionmentioning
confidence: 99%
“…The 2 nd highest number of cases from 2009 to 2013 was in Eastern Visayas, which is also endemic for soil-transmitted helminthiases (Leyte) and is the top region with poor sanitation. 44 The UNICEF has reported that sanitation targets in the Philippines, together with the rest of the world, are off-track from the goal to provide sanitation for all by 2030. 45 A recent typhoon in Southern Leyte required concerted efforts to restore access to clean water and sanitation facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 800 million people, especially children, are at risk for getting schistosomiasis, leading to 250 million infections worldwide [ 1 ]. Prevalence of this disease varies from region to region, for example, 90.6% in north-western Tanzania [ 2 ], 40% in south-western Nigeria [ 3 ], 37.38% in Jiangsu Province, China [ 4 ], 8.4% in The Philippines [ 5 ] 4.9–8.1% in north-eastern Brazil [ 6 ], and 0.6% in Puerto Rico [ 7 ]. The burden of Schistosoma infection is substantial, including 1,430,000 disability adjusted life year (DALY) per year globally and 280,000 deaths in Sub Saharan Africa region annually [ 1 ].…”
Section: Introductionmentioning
confidence: 99%